Assessment and Classification of Indian Soybean [(Glycine max L.) Merr] Varieties for their Response to Field Weathering - V.S. BHATIA,; SANJEEV YADAV,; K.N. GURUPRASAD, (Seed Research, 2026)
Assessment of sixty-two Indian soybean [Glycine max (L.) Merr.] varieties were done for their response to field weathering and further classified on the basis of seedling vigour index as affected by field weathering. The assessment was made after exposing the standing crop to ambient weather conditions by delaying the harvesting for three weeks. For field weathering treatment, soybean pods were manually harvested three weeks after physiological maturity, while control (unweathered) pods were harvested at physiological maturity. Field weathering adversely affects the standard germination, normal seedling growth and finally seedling vigour index. In the present study the average reduction in the SG and SVI value was 20 and 33.2%, and ranged from 1 to 63% and 2.7 to 76%, respectively among these varieties, when the harvesting was delayed by 3 weeks as compared to their corresponding unweathered seeds. The classification of field weathering tolerant/susceptible varieties would be beneficial for selection of a variety for cultivation in tropical climate, where the adverse weather conditions for soybean are prevelent at the time of harvesting. The tolerant varieties can be used for breeding programme for improvement of the varieties.